Pmp22 super-enhancer deletion causes tomacula formation and conduction block in peripheral nerves. (30th April 2020) - Pantera, Harrison; Hu, Bo; Moiseev, Daniel; Dunham, Chris; Rashid, Jibraan; Moran, John J; Krentz, Kathleen; Rubinstein, C Dustin; Won, Seongsik; Li, Jun; Svaren, John
Abstract: Copy number variation of the peripheral nerve myelin gene Peripheral Myelin Protein 22 ( PMP22 ) causes multiple forms of inherited peripheral neuropathy. The duplication of a 1.4 Mb segment surrounding this gene in chromosome 17p12 (c17p12) causes the most common form of Charcot-Marie-Tooth disease type 1A, whereas the reciprocal deletion of this gene causes a separate neuropathy termed hereditary neuropathy with liability to pressure palsies (HNPP). PMP22 is robustly induced in Schwann cells in early postnatal development, and several transcription factors and their cognate regulatory elements have been implicated in coordinating the gene's proper expression. We previously found that a distal super-enhancer domain was important for Pmp22 expression in vitro, with particular impact on a Schwann cell-specific alternative promoter. Here, we investigate the consequences of deleting this super-enhancer in vivo . We find that loss of the super-enhancer in mice reduces Pmp22 expression throughout development and into adulthood, with greater impact on the Schwann cell-specific promoter. Additionally, these mice display tomacula formed by excessive myelin folding, a pathological hallmark of HNPP, as have been previously observed in heterozygous Pmp22 mice as well as sural biopsies from patients with HNPP. Our findings demonstrate a mechanism by which smaller copy number variations, not including the Pmp22 gene, are sufficient to reduce gene expression and phenocopy a peripheral neuropathy caused by the HNPP-associated deletion encompassing PMP22 .